On the Accentuation of the Earliest Latin Loanwords in Slavic - Matasović, Ranko (Array, 2007)
The paper deals with the accentuation of the earliest Latin loanwords in Slavic and establishes their relative chronology. It also shows how they are distributed according to Slavic accentual paradigms.